Waste reduction of polypropylene bag manufacturing process using Six Sigma DMAIC approach: A case study. Issue 1 (1st January 2021) - Sajjad, Muhammad Hamad; Naeem, Khawar; Zubair, Muhammad; Usman Jan, Qazi Muhammad; Khattak, Sikandar Bilal; Omair, Muhammad; Nawaz, Rashid
Abstract: In the current study, minimization of waste in terms of sack rejection at a polypropylene bag manufacturing process is achieved. The Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) approach is adopted which results in 50% waste reduction and a considerable cost saving. The sack rejection is brought to 1.20% from the previous average waste of 2.80% using DMAIC. It is found that this high rejection rate of 2.80% is due to the low fabric strength obtained at the weaving section, which in turn occurred due to the lower tape tenacity values obtained from the extrusion section. Hence, experimental design is conducted at the extrusion department and it is found that the two interacting factors are playing a significant contribution to the process variation and hence result in lower tape-tenacity (i.e., less than 6 g/denier). The two interacting factors included the "water bath temperature" and "line speed" of the extrusion process, with a p-value less than 5%. By further analysis, the optimal level of these significant factors is found. They are 300 m/min for "line speed" and 40⁰C for "water bath temperature. At these settings, the extrusion process produces optimal tape-tenacity results (i.e., at least 6 g/denier), which ultimately results in minimum waste in terms of sack rejection waste. The objective of the study includes finding the significant factors contributing to the process variation. Also controlling those factors to the optimal levels to achieve minimum wastage and considerable cost saving. The methodology and findings of the present study can be generalized to the polypropylene bag manufacturing plants and the process efficiency can be enhanced.